Clinical assessment of nutritional status of term newborns at birth using CANSCORE. - Umesh, J.; Sridhar, N.L. (European Journal of Pediatric Dermatology, 2018)
Since maternal malnutrition is a probable cause of fetal malnutrition (FM), it is important to assess the nutritional status of the mother in mid pregnancy to predict births of malnourished babies. If SGA (small for gestational age) can be detected in utero during 2nd or early 3rd trimester using ultrasound for prediction of fetal growth, such as that devised by Rossavik (18), Deter et Al. (2, 3, 4) and cordocentesis used to obtain umblical blood for concentrations of nutrients in plasma and cells, specific intrauterine nutrition therapies for the malnourished fetuses could be implemented to prevent malnutrition at birth. Fetal malnutrition, a term coined by Scott (21) and Usher (27), indicates a clinical state that may be present at almost any birth weight, irrespective of classification of infants as appropriate for gestational age (AGA), SGA or intrauterine growth retardation (IUGR). Fetal malnutrition, the term small for gestational age and intrauterine growth retardation are not synonymous (17) and one may occur without the others (20, 26, 27, 28). SGA is weight for gestational age based on population norms and some predetermined weight cut off, -2SD, 5%, 10%- (17, 22, 27, 28). IUGR refers to a multiplicity of adverse effects limiting the fetal growth potential (17). An infant who is classified IUGR may or may not be classified SGA (17). Likewise an infant who is IUGR and /or SGA may or may not have FM (11, 14, 16, 17). FM affects body composition, impairs brain development and behavior in experimental animals (1). It’s effect on brain and mental development in humans remains controversial (6, 7, 8, 9, 11, 15, 19 23, 24, 25) confounded by many factors including failure to differentiate between SGA and malnutrition in the newborn.